Tuberous sclerosis complex, Serbian referral center experience - Kosać Ana; Jović Nebojša J. (Vojnosanitetski Pregled)
BackgroundAim. Common features of tuberous sclerosis complex (TSC) arise from the formation of hamartomas both in the brain and multiple organ systems, mainly due to a mutation in one of two genes, TSC1 or TSC2, with well described inter- and intrafamilial different phenotypic outcomes. The aim of this work was to make a synthesis of the patients data with diagnosed tuberous sclerosis in order to better understand the disease in our environment. Methods. We reviewed retrospectively the clinical records of all patients with TSC, diagnosed and regularly followed at the Clinic of Neurology and Psychiatry for Children and Youth in Belgrade, Serbia during the period of more than two decades. Statistical analyses were performed using descriptive statistics as well as the Fisher’s exact test. Results. Cohort of 44 patients with the diagnosis of definitive TSC were included. The mean age at last follow-up was 19.4 years [age range 1–58, standard deviation (SD) 11.8]. Family history for TSC was noted in 25% of patients. Dermatological manifestations were described in 93.2%, retinal astrocytoma and cardiac rhabdomyomas was found in 36.4% each, nephrological manifestations in 34.1% and lymphangioleiomyomatosis was diagnosed in two female patients. All patients presented with the structural lesions of central nervous system; epilepsy was diagnosed in 88.6%, out of whom 59 % of patients had seizure onset in the first year of life. The West syndrome was diagnosed in 27.3% of patients. Complete seizure control was achieved in 30.8%, in a majority with valproic acid or cabamazepine, but also with topiramate, lamotrigine and vigabatrin. At least two antiepileptic drugs were administered in 82% of patients. Mental retardation was noted in 50% of patients. Psychiatric manifestations were found in 40.9%, with attention deficit hyperactivity disorder diagnosed in 27.3%, autism spectrum disorder in 13.6 %, and psychosis and depression observed in 11.4% each. Conclusion. This kind of synthesis of the data certainly contributes to better understanding of the disease in our environment, as TSC, although well-known disease, still remains diagnostic and therapeutic challenge in daily clinical practice.